2015
DOI: 10.1103/physrevb.92.241105
|View full text |Cite
|
Sign up to set email alerts
|

Interface between heavy fermions and normal electrons investigated by spatially resolved nuclear magnetic resonance

Abstract: We have studied the superlattices with alternating block layers (BLs) of heavy-fermion superconductor CeCoIn5 and conventional-metal YbCoIn5 by site-selective nuclear magnetic resonance(NMR) spectroscopy, which uniquely offers spatially-resolved dynamical magnetic information. We find that the presence of antiferromagnetic fluctuations is confined to the Ce-BLs, indicating that magnetic degrees of freedom of f -electrons are quenched inside the Yb-BLs. Contrary to simple expectations that the two-dimensionaliz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 25 publications
(24 reference statements)
4
27
0
Order By: Relevance
“…Thus, the model captures qualitative properties of these materials although a significantly simplified model is adopted. The suppression of magnetic fluctuation by the ASOC is a generic feature [16], and it has been confirmed by a NMR experiment in CeCoIn 5 superlattices [92]. A qualitatively same conclusion is obtained from noninteracting magnetic susceptibility (see Fig.…”
Section: Magnetic Fluctuationsupporting
confidence: 74%
“…Thus, the model captures qualitative properties of these materials although a significantly simplified model is adopted. The suppression of magnetic fluctuation by the ASOC is a generic feature [16], and it has been confirmed by a NMR experiment in CeCoIn 5 superlattices [92]. A qualitatively same conclusion is obtained from noninteracting magnetic susceptibility (see Fig.…”
Section: Magnetic Fluctuationsupporting
confidence: 74%
“…Moreover, the large Fermi velocity mismatch across the interface between heavy-fermion and nonmagnetic metal layers significantly reduces the transmission probability of heavy QPs [5]. In fact, it has been shown that the superconducting heavy QPs as well as the magnetic fluctuations are well confined within the 2D Ce-BLs, as revealed by recent studies of upper critical field and site-selective nuclear magnetic resonance [6,7]. Quantum fluctuations are expected to be more pronounced in reduced spatial , the effect of reduced dimensionality would be more prominent in the present superlattices based on the tetragonal CeRhIn 5 with lower T N .…”
mentioning
confidence: 88%
“…Here, in the n = 3 superlattice, the inversion symmetry is locally broken at the top and bottom layers of the CeRhIn 5 blocks in the immediate proximity to the YbRhIn 5 layers, whereas the symmetry is preserved in the middle layer [7,[9][10][11]. In the 5 absence of inversion symmetry, asymmetry of the potential in the direction perpendicular to In the presence of the local inversion symmetry breaking at the interfaces, the magnetic anisotropy is expected to be modified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent siteselective NMR spectroscopy experiments have also indicated that the local ISB affects the magnetic properties, leading to the suppression of AFM fluctuations. 37 Thus, the interfacial effect becomes a key element for understanding the electronic state in the CeCoIn 5 /YbCoIn 5 superlattices. The details of these experiments are given in the following subsections.…”
Section: Local Inversion Symmetry Breakingmentioning
confidence: 99%